Characterisation of the Kynurenine Pathway in Skin‐Derived Fibroblasts and Keratinocytes. Issue 6 (10th April 2015) - Sheipouri, Diba; Grant, Ross; Bustamante, Sonia; Lovejoy, David; Guillemin, Gilles J.; Braidy, Nady
ABSTRACT: Acute UVB exposure triggers inflammation leading to the induction of indoleamine 2, 3 dioxygenase (IDO1), one of the first enzymes in the kynurenine pathway (KP) for tryptophan degradation. However, limited studies have been undertaken to determine the catabolism of tryptophan within the skin. The aim of this study was two fold: (1) to establish if the administration of the proinflammatory cytokine interferon‐gamma (IFN‐γ) and/or UVB radiation elicits differential KP expression patterns in human fibroblast and keratinocytes; and (2) to evaluate the effect of KP metabolites on intracellular nicotinamide adenine dinucleotide (NAD + ) levels, and cell viability. Primary cultures of human fibroblasts and keratinocytes were used to examine expression of the KP at the mRNA level using qPCR, and at the protein level using immunocytochemistry. Cellular responses to KP metabolites were assessed by examining extracellular lactate dehydrogenase (LDH) activity and intracellular NAD + levels. Major downstream KP metabolites were analyzed using GC/MS and HPLC. Our data shows that the KP is fully expressed both in human fibroblasts and keratinocytes. Exposure to UVB radiation and/or IFN‐γ causes significant changes in the expression pattern of downstream KP metabolites and enzymes. Exposure to various concentrations of KP metabolites showed marked differences in cell viability and intracellular NAD + production, providing support for involvement of the KP in the de novo synthesis of NAD + in the skin. This new information will have a significant impact on our understanding of the pathogenesis of UV related skin damage and the diagnosis of KP related disease states. J. Cell. Biochem. 116: 903–922, 2015. © 2015 Wiley Periodicals, Inc.